Analysis of the Teacher’s Role in Enhancing Students’ Critical Thinking Skills: Social Studies Learning at Elementary School - Zarniati Zarniati; Samuel Patra Ritiauw; Leonid Ritiauw (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Critical thinking skills are essential competencies in Social Studies (IPS) learning, yet their development depends heavily on the teacher's classroom efficacy. At Elementary School 2 Ambon, a comprehensive understanding is required regarding how teachers integrate their pedagogical responsibilities to stimulate students' critical thinking. This study aims to investigate and describe the teacher's role in improving students' critical thinking skills through IPS learning at Elementary School 2 Ambon. Utilizing a qualitative approach with descriptive methods, the research subjects included the principal, IPS teachers, and 20 students. Data were collected via observation, interviews, and documentation techniques, and analyzed using the Miles and Huberman interactive model (data collection, reduction, display, and conclusion drawing). The findings reveal that teachers effectively perform seven main functions to foster critical thinking: (1) Educator, providing quality instructions; (2) Demonstrator, utilizing learning media; (3) Class Manager, maintaining a conducive atmosphere; (4) Facilitator, supplying learning resources; (5) Supervisor, directing student activities; (6) Motivator, providing encouragement; and (7) Evaluator, conducting test and non-test assessments. Practically, this research guides educators on diversifying instructional roles to optimize students' cognitive abilities. Theoretically, these results enrich the literature on pedagogical strategies in elementary social studies to cultivate a critical and analytical generation.